Paternal involvement and its influence on children's educational achievement - Fernandez, Johann Ray J.; Reandelar, Joanne F. (2005.)
Te influence of paternal involvement on children's educational achievement was explored in this study using qualitative and quantitative research methods. The roles fulfilled by the fathers were determined and how variables such as educational attainment and income affect the extent of their involvement in relation to their children's schooling. Thirty first year high school students and their respective fathers participated in the study. The students were randomly selected from two sections with differences in their grade averages. Four categories of paternal involvement in children's education emerged from this study, namely: financial support provider; moral advisor; co-teacher; and support & encouragement provider, It was also found that most fathers perceive their level of involvement in their children's education was average. This indicates that parental tasks belonging to the financial support provider, moral advisor and co-teacher are commonly performed. Results of the study also confirmed that paternal involvement influences educational achievement of children. Children, with fathers having high paternal involvement, have higher educational achievement than children whose fathers are less involved in their children. Fathers found to have high level involvement in their children's education have higher educational attainment and income than fathers with low level of involvement, suggesting that educational attainment and income of fathers affect their level of involvement in their children's education. The results confirming the influence of paternal involvement in children's educational achievement provided a sound support for recommending the development and promotion of school programs and activities that would increase the involvement of fathers in their children's education.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Education -- Parent participation -- Philippines; Father and child -- Philippines